2013
DOI: 10.1111/j.1445-5994.2013.02864.x
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis following hip and knee arthroplasty

Abstract: Aim To determine local thromboprophylaxis prescribing practices following arthroplasty. Methods A retrospective review was performed of 300 consecutive hip and knee arthroplasty patients (150 each) over a 2‐year period at Tasmania's major public hospital. The provision of thromboprophylaxis, the presence of bleeding/thrombotic risk factors and the prevalence of symptomatic venous thromboembolism (VTE) and major bleeding occurring within 90 days postoperatively were documented. Results The mean age of the 300 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 127 publications
1
9
0
Order By: Relevance
“…Less commonly encountered reasons included prescription of subtherapeutic dose (4%, 4/101) and prescription of an agent not recommended for thromboprophylaxis (1%, 1/101). This is consistent with previous reports where inadequate duration of chemoprophylaxis was a commonly cited reason for poor adherence to accepted guidelines . It is recognised that the risk of VTE extends beyond the period of hospitalisation and in our study, 25.8% (98/380) of patients received no chemoprophylaxis on discharge, suggesting that re‐assessment of duration of chemoprophylaxis prescription represents an area of potential improvement.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Less commonly encountered reasons included prescription of subtherapeutic dose (4%, 4/101) and prescription of an agent not recommended for thromboprophylaxis (1%, 1/101). This is consistent with previous reports where inadequate duration of chemoprophylaxis was a commonly cited reason for poor adherence to accepted guidelines . It is recognised that the risk of VTE extends beyond the period of hospitalisation and in our study, 25.8% (98/380) of patients received no chemoprophylaxis on discharge, suggesting that re‐assessment of duration of chemoprophylaxis prescription represents an area of potential improvement.…”
Section: Discussionsupporting
confidence: 92%
“…Previous Australian studies have reported that mechanical thromboprophylaxis continues to be underused . A recent study evaluating patients undergoing TKA and THA at an Australian public hospital revealed that over 60% of patients did not receive any form of documented thromboprophylaxis on discharge, and only 35% received chemoprophylaxis on discharge . The results of our study show a higher proportion of patients receiving prophylaxis on discharge, with 74.5% (283/380) of eligible patients receiving chemoprophylaxis on discharge.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Rates of VTE after total knee arthroplasty (TKA) and total hip arthroplasty (THA) have been reported to be between 40 and 94 and 13 and 24 per 1,000 patients, respectively. 7 9 With an aging population, the overall incidence and impact of VTE after arthroplasty are expected to increase substantially over the next few decades. For instance, the number of THA and TKA procedures have been increasing at 3.7% and 7.0% per year in Australia.…”
Section: Introductionmentioning
confidence: 99%